H.L. von Collin - Lange, Joseph (artist):::Creator::::::::::::; Bolt, Johann Friedrich (engraver):::Contributor:::::::::::: (Germany; Gebrüder Schumann; Zwickau)
Half-length, full-face portrait engraving of Heinrich Joseph von Collin.